Analysis of Drosophila Atg8 proteins reveals multiple lipidation-independent roles. - Jipa, A.; Vedelek, V.; Merényi, Z.; Ürmösi, A.; Takáts, S.; Kovács, A.L.; Horváth, G.V.; Sinka, R.; Juhász, G. (Autophagy, 2021)
Yeast Atg8 and its homologs are involved in autophagosome biogenesis in all eukaryotes. These are the most widely used markers for autophagy thanks to the association of their lipidated forms with autophagic membranes. The Atg8 protein family expanded in animals and plants, with most Drosophila species having two Atg8 homologs. In this Brief Report, we use clear-cut genetic analysis in Drosophila melanogaster to show that lipidated Atg8a is required for autophagy, while its non-lipidated form is essential for developmentally programmed larval midgut elimination and viability. In contrast, expression of Atg8b is restricted to the male germline and its loss causes male sterility without affecting autophagy. We find that high expression of non-lipidated Atg8b in the male germline is required for fertility. Consistent with these non-canonical functions of Atg8 proteins, loss of Atg genes required for Atg8 lipidation lead to autophagy defects but do not cause lethality or male sterility.